The overstated generational gap in online news use? A consolidated infrastructural perspective. (October 2022) - Mangold, Frank; Stier, Sebastian; Breuer, Johannes; Scharkow, Michael
Recent research by Taneja et al. suggested that digital infrastructures diminish the generational gap in news use by counteracting preference structures. We expand on this seminal work by arguing that an infrastructural perspective requires overcoming limitations of highly aggregated web tracking data used in prior research. We analyze the individual browsing histories of two representative samples of German Internet users collected in 2012 ( N = 2970) and 2018 ( N = 2045) and find robust evidence for a smaller generational gap in online news use than commonly assumed. While short news website visits mostly demonstrated infrastructural factors, longer news use episodes were shaped more by preferences. The infrastructural role of social media corresponded with reduced news avoidance and more varied news repertoires. Overall, the results suggest that research needs to reconsider commonly held premises regarding the uses of digital media in modern high-choice settings.